Framing an Integrative Approach to the Education and Development of Teachers in Canada - Falkenberg, Thomas (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
The education of teachers in Canada typically consists of a sequence of non-integrated and partially alternating phases: pre-service university-based course work, pre-service school-based practica, job-imbedded induction, professional development sessions. This article proposes an integrative approach to the education of teachers that links these different phases: Collaborative Professional Development Centres. The article draws on teacher education scholarship and research to articulate a number of assumptions about learning to teach and the purpose of teacher education, and then argues (a) that the traditional non-integrated approach to the education of teachers is incompatible with these assumptions, and (b) that these assumptions provide an excellent framework for the idea of Collaborative Professional Development Centres.